THE IMPORTANCE OF SCIENTIFIC INFORMATION AND ITS USE IN TEACHING GEOGRAPHY - Zhumabaeva Gulsim Kairatovna; Laiskhanov Shakhislam Uzakbaevich (Reviews of Modern Science, 2025)
The article discusses the role of scientific information in the educational process and its effective application in teaching geography. Scientific information helps students to deepen their understanding of geographical phenomena, develop critical thinking and analytical skills, as well as shape a scientific worldview. The use of scientific data enhances students’ research skills and enables them to gain a deeper understanding of natural and social processes. The article emphasizes the necessity of increasing the accessibility of scientific information in the educational process through the use of digital resources and innovative platforms. Geographic Information Systems (GIS), virtual maps, electronic textbooks, and online platforms make the learning process interactive and visual, thereby increasing students’ interest in the subject. Research shows that teaching methods based on scientific information not only improve the quality of education but also encourage students to engage in independent research. These methods foster students’ ability to analyze geographical phenomena deeply. Therefore, the systematic and purposeful use of scientific information in geography teaching is one of the important factors in enhancing the professional competencies of future specialists.